Improving Leadership Skills Through Supervisory Leadership Training at J&T Express Jawa Timur - Saputro, Oki Dwi; Atmadja J.A, I Ketut; Widodo, Widodo (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This study aims to evaluate the effectiveness of the Supervisory Leadership Training program in enhancing the leadership skills of supervisors at J&T Express East Java. Utilizing a quantitative approach with a one-group pretest-posttest design, data were collected through questionnaires administered before and after the training. The analysis results indicate an improvement in leadership skills following the training, with the average score increasing from 163.5445 in the pre-test to 167.0034 in the post-test, reflecting an increase of 3.4589 points. This 2.11% increase serves as strong evidence of the training’s effectiveness in enhancing supervisors' leadership skills. The statistical test using the Paired Sample t-Test confirmed that this improvement is statistically significant (p < 0.05). The most notable improvements were observed in task delegation and communication aspects. The validity and reliability of the research instrument were also confirmed through factor analysis and Cronbach’s Alpha test. In conclusion, the Supervisory Leadership Training program has been proven effective in improving supervisors' leadership skills. This finding suggests that the Supervisory Leadership Training program can serve as a solid foundation for developing similar training programs in the future to enhance supervisory leadership competencies across various industrial sectors.